2013
DOI: 10.1007/s12038-013-9298-7
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of nonsyndromic cleft lip with or without cleft palate in females: Is homocysteine a factor?

Abstract: In India, as in other parts of the world, nonsyndromic cleft lip with or without cleft palate (NSCL +/- P) is a highly prevalent birth defect, its incidence in males being twice that in females. A case-control association study has been carried out with respect to homocysteine level and MTHFR C677T, A1298C and SLC19A1 (RFC1) G80A genotypes from an eastern Indian cohort to investigate whether Hcy and other Hcy-pathway genes also contribute to the risk level. While MTHFR 677T and SLC19A1 80G are individually and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 22 publications
0
31
1
Order By: Relevance
“…This study concludes that both in children and adolescence, homocysteine levels are influenced by ethnicity, of which plasma concentration of homocysteine in black people are higher than whites or Hispanics. 15 Another study which was conducted by Kumari et al 16 in East India, which is an area of folate and vitamin B12 deficiencies, showed that the average homocysteine levels in normal male children were 13.2 (9.7 to 16.7) µmol/L while in female children the levels were 11.7 (7.7 to 16) µmol/L. In a study conducted by Sirachainan et al17 in 2008 in normal children in Thailand, the mean homocysteine level was 11 µmol/L.…”
Section: Relationship Between C677t Methylenetetrahydrofolate Reductamentioning
confidence: 99%
“…This study concludes that both in children and adolescence, homocysteine levels are influenced by ethnicity, of which plasma concentration of homocysteine in black people are higher than whites or Hispanics. 15 Another study which was conducted by Kumari et al 16 in East India, which is an area of folate and vitamin B12 deficiencies, showed that the average homocysteine levels in normal male children were 13.2 (9.7 to 16.7) µmol/L while in female children the levels were 11.7 (7.7 to 16) µmol/L. In a study conducted by Sirachainan et al17 in 2008 in normal children in Thailand, the mean homocysteine level was 11 µmol/L.…”
Section: Relationship Between C677t Methylenetetrahydrofolate Reductamentioning
confidence: 99%
“…The genotype and allele distributions are as shown in Table 2. Only in four studies (Shoteresuk et al, 2003;van Roij et al, 2003;SemicJusufagic et al, 2012;Kumari et al, 2013), OR was above one and in other seven studies did not show any association between MTHFR A1298C polymorphism and OFC. The distribution of genotypes in the control groups were in Hardy-Weinberg equilibrium (HWE) in all studies.…”
Section: Discussionmentioning
confidence: 91%
“…Eleven articles were found to be eligible for the inclusion in the present meta-analysis Grunert et al, 2002;Shoteresuk et al, 2003;van Roij et al, 2003;Pezzetti et al, 2004;Mills et al, 2008;Ali et al, 2009;Sozen et al, 2009;Chorna et al, 2011;SemicJusufagic et al, 2012;Kumari et al, 2013). All these eleven studies were performed in different countries: Argentina , Germany (Grunert et al, 2002), India (Ali et al, 2009;Kumari et al, 2013), Ireland (Mills et al, 2008), Italy (Pezzetti et al, 2004), Netherlands (van Roij et al, 2003), Thailand (Shoteresuk et al, 2003), Ukraine (Chorna et al, 2011), and Venezuela (Sozen et al, 2009).…”
Section: Eligible Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blanco et al [2] found results that support the hypothesis that genetic variation in the MSX1 gene may be linked to this higher susceptibility of males. Kumari et al [11] suggested that homocysteine level threshold necessary to manifest cleft lip with or without cleft palate in female is much higher than in males, which may be one reason why the frequency of females is smaller than in males. However, further molecular and genetic studies are necessary for a better understanding of the differences between the cleft types and gender.…”
Section: Discussionmentioning
confidence: 99%